Askin tumor: Case report and literature review - Cueto Ramos, Rubén Gerardo; Ponce Escobedo, Aurora Natalia; Montero Cantú, Carlos Alberto; Muñoz Maldonado, Gerardo Enrique; Ruiz Holguín, Eduardo; Viches Cisneros, Natalia (UANL. Facultad de Medicina, 2015)
Askin tumor is an uncommon malignant neoplasm of a neuroectodermic origin that arises from the soft tissues of the thoracopulmonary wall. Defined histologically by Askin and Rosai in 1979 as a malignant small round cell tumor. It is described within a group of malignant neoplasms with an aggressive behavior. The lack of clinical guides that establish a standardized management contributes to its poor prognosis and short overall survival. Once a primitive neuroectodermal tumor has been diagnosed, treatment will consist of a multimodal management.